2009
DOI: 10.1097/prs.0b013e3181bf7e1b
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Three-Dimensional, Normative Database of Pediatric Craniofacial Morphology for Modern Anthropometric Analysis

Abstract: Three-dimensional vector analysis provides accurate, comprehensive description of cranial morphology with quantitative graphic output. The method enables development of an extensive pediatric normative craniofacial database. Future application of these data will facilitate analysis of cranial anomalies and assist with clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 18 publications
0
67
0
5
Order By: Relevance
“…However, in contrast to the data reported by Saber et al, 48 or Marcus et al, 34,35 our database also provides the opportunity to perform long-term evaluation of the performed surgery, based on sound 3D measurements up to the age of 20 years. Our database allows for thorough evaluation of the surgical result in a specific patient over time, by providing age-specific normative data and allowing for a comparison with what is considered "normal."…”
Section: Two-dimensional and 3d Measurementsmentioning
confidence: 59%
See 3 more Smart Citations
“…However, in contrast to the data reported by Saber et al, 48 or Marcus et al, 34,35 our database also provides the opportunity to perform long-term evaluation of the performed surgery, based on sound 3D measurements up to the age of 20 years. Our database allows for thorough evaluation of the surgical result in a specific patient over time, by providing age-specific normative data and allowing for a comparison with what is considered "normal."…”
Section: Two-dimensional and 3d Measurementsmentioning
confidence: 59%
“…34 In their subsequent report, Marcus et al demonstrated this technique but limited the presentation of their normative data to essentially 2D measurements: cephalic width, cephalic length, and the calculated cephalic index. 35 It would be very interesting to compare any explicit 3D measurements derived from their database with the data presented in this study.…”
Section: Two-dimensional and 3d Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of 3D surface scanners and increased computing power it is now possible to capture and process spatially dense facial surfaces, but reported rigid surface registrations departed from conventional facial anthropometrics by not maintaining anatomical relationships during the comparative analysis 9,[11][12][13]24,25 . This severely limits its use and fails to inform the clinician of what must be achieved for a good clinical outcome.…”
Section: Discussionmentioning
confidence: 99%